2010
DOI: 10.1002/ange.201006218
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Oxygen Preference in Enolate Monofluoromethylation and a Synthetic Entry to Monofluoromethyl Ethers

Abstract: The control of regioselectivity in the alkylation of enolates is one of the oldest research areas in organic chemistry. [1] The ratio of regioisomers formed by C/O-alkylation is sensitive to the extent of substrate enolization, which is highly dependent on the structure of the carbonyl compound, but also on the nature of the alkylating reagent and the reaction conditions, in particular the solvent and base. It has been shown that more C-alkylation tends to be observed with softer nucleophiles, whereas O-alkyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 59 publications
0
18
0
2
Order By: Relevance
“…Da das Reagens 2.1 durch Alkylierung von Natriumthiophenolat mit Chlorfluormethan hergestellt wird, ist eine Fluormethylierung mit Chlorfluormethan effizienter und kann mit reaktiven Substraten wie Phenolen, Thiophenolen und Imidazolen ähnliche Ausbeuten liefern. [ [176] Eine elektrophile Fluormethylierung von Arylnucleophilen wurde unseres Wissens bisher noch nicht beschrieben.…”
Section: Elektrophile Methoden Der Fluormethylierungunclassified
See 1 more Smart Citation
“…Da das Reagens 2.1 durch Alkylierung von Natriumthiophenolat mit Chlorfluormethan hergestellt wird, ist eine Fluormethylierung mit Chlorfluormethan effizienter und kann mit reaktiven Substraten wie Phenolen, Thiophenolen und Imidazolen ähnliche Ausbeuten liefern. [ [176] Eine elektrophile Fluormethylierung von Arylnucleophilen wurde unseres Wissens bisher noch nicht beschrieben.…”
Section: Elektrophile Methoden Der Fluormethylierungunclassified
“…Die nucleophile Fluormethylierung von Elektrophilen basiert auf der Verwendung von Fluormethidäquivalenten, die normalerweise mesomere stabilisierende Gruppen, beispielsweise Sulfone, enthalten. [ [176] Eine elektrophile Fluormethylierung von Arylnucleophilen wurde unseres Wissens bisher noch nicht beschrieben. Auch das seltene Beispiel einer radikalischen Fluormethylierung wurde beschrieben.…”
Section: Fluormethylierungunclassified
“…They concluded that the enolate ion of 1 a attacks at the methyl carbon atom of the sulfonium salts through an ionic S N 2 process after the formation of a S—O sulfurane intermediate (Scheme 2). [10] In this context, our findings of complete C selectivity in trifluoromethylation5c and O selectivity in monofluoromethylation3h are of great interest not only for the synthesis of fluorinated compounds but also for the mechanistic aspect of alkylations. The number of fluorine atoms should have an effect on C and O selectivities.…”
mentioning
confidence: 86%
“…It has been shown that C-alkylation tends to be observed more frequently with softer electrophiles, while O-alkylation is preferred with harder electrophiles. [8, 9] However, the complete control of C/O regioselectivity is still a challenge, for example, in the O-regioselective methylation of β-ketoesters 3h,. [9, 10] Matsuyama and co-workers carefully examined the methylation of methyl 1-indanone-2-carboxylate ( 1 a ) using two types of methyl sulfonium salts A and B in the presence of K 2 CO 3 in dichloromethane.…”
mentioning
confidence: 99%
“…[810] Electrophilic difluoromethylation through difluorocarbene species has attracted considerable attention, and several methods have been reported 8ah, j, l. Although the difluoromethylation of heteroatom-centered nucleophiles such as oxygen, sulfur and nitrogen nucleophiles is well studied,[11], 8g, j, l mild and efficient difluoromethylation methods for carbon-centered nucleophiles are relatively scarce 8i, km, 12d. In 2007, Prakash and co-workers developed a new electrophilic difluoromethylating reagent, S -(difluoromethyl)diarylsulfonium tetrafluoroborate 8i.…”
mentioning
confidence: 99%